New Synthesis of 2′,4′-Functionalized Nucleotides via Stereospecific Hydrogenation and Azidation Reactions - Houpis, Ioannis N.; Lemaire, Sebastien; Farina, Vittorio; Xiao, Tingting; Liu, Renmao; Nettekoven, Ulrike; Wang, Youchu (Synlett, 2013)
The synthesis of an anti-infective nucleoside derivative was accomplished through selective hydrogenation using an achiral ligand to establish the stereochemistry of the 2′ stereogenic center. The quaternary 4′ center was introduced through stereoselective epoxidation with dimethyl dioxirane followed by a regioselective, stereospecific epoxide opening with trimethylsilyl azide.
Keywords: homogeneous hydrogenation; nucleotide synthesis; dimethyl dioxirane; azides